High gene flow despite opposite chirality in hybrid zones between enantiomorphic door snails. Issue 15 (27th May 2017) - Koch, Eva L.; Neiber, Marco T.; Walther, Frank; Hausdorf, Bernhard
Abstract: We studied differentiation and geneflow patterns between enantiomorphic door‐snail species in two hybrid zones in the Bucegi Mountains (Romania) to investigate the effects of intrinsic barriers (complications in copulation) and extrinsic selection by environmental factors. A mitochondrial gene tree confirmed the historical separation of the examined populations into the dextral Alopia livida and the sinistral Alopia straminicollis in accordance with the morphological classification, but also indicated gene flow between the species. By contrast, a network based on amplified fragment length polymorphisms (AFLP) markers revealed local groups of populations as units independent of their species affiliation. Admixture analyses based on AFLP data showed that the genomes of most individuals in the hybrid zones are composed of parts of the genomes of both parental taxa. The introgression patterns of a notable fraction of the examined markers deviated from neutral introgression. However, the patterns of most non‐neutral markers were not concordant between the two hybrid zones. There was also no concordance between non‐neutral markers in the two genomic clines and markers that were correlated with environmental variables or markers that were correlated with the proportion of dextral individuals in the populations. Neither extrinsic selection by environmental factors nor intrinsic barriers resulting from positive frequency‐dependent selection of the prevailing coiling direction were sufficient to maintain the distinctness of A. straminicollis and A. livida . Despite being historically separated units, we conclude that these taxa now merge where they come into contact.